"Made of Sterner Stuff": Female Agency and Resilience in Nadifa Mohamed's The Orchard of Lost Souls. Issue 3 (3rd July 2019) - Tembo, Nick Mdika
Summary: The focus of this article is on the literary representations of women in postcolonial wartime narratives by African female novelists. An important assumption drives this article, namely, that women are largely absent from discussions on the interventions they can make to help fight social injustice, even though violence and resistance to injustice are mostly mediated through images of women and their bodies. Specifically, the article examines how Nadifa Mohamed employs agency as a discursive technique for negotiating female identities and dismantling oppressive structures in The Orchard of Lost Souls . The article is cognizant of Annie Gagiano's views that recent African female authors' novels have gained prominence in tackling national(ist) issues through their imagination of the nation with moral profundity and historical force, placing the women themselves at the centre of this national imagination. I argue that the leading female characters in Mohamed's novel reconstruct their subalternity all too predictably to fight gendered violence and social vice, thereby contributing to the nationalist fervour that is underway in the narrative context of the novel.